Transformation ratio at excitation of nonlinear wakefield in plasma by shaped sequence of electron bunches with linear growth of charge - Maslov, V.I.; Onishchenko, I.N.; Yarovaya, I.P. (Вопросы атомной науки и техники, 2012)
Using code LCODE, the 2d3v-numerical simulation of nonlinear wakefield excitation in plasma by shaped sequence of relativistic electron bunches with linear growth of charge has been performed. The transformation ratio has been determined taking into account nonlinearity of excited wakefield at shaping of bunches and sequence. Используя код LCODE, проведено 2d3v-численное моделирование возбуждения нелинейной кильватерной волны в плазме профилированной последовательностью релятивистских электронных сгустков с линейно нарастающей интенсивностью. Определен коэффициент трансформации с учетом нелинейности возбуждаемой кильватерной волны при профилировании сгустков и последовательности. Використовуючи код LCODE, проведено 2d3v-чисельне моделювання збудження нелінійної кільватерної хвилі в плазмі профільованою послідовністю релятивістських електронних згустків з лінійно наростаючей інтенсивністю. Визначен коефіцієнт трансформації з урахуванням нелінійності збуджуваної кільватерної хвилі при профілюванні згустків і послідовності.